2004
DOI: 10.3748/wjg.v10.i21.3197
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor immunity induced by DNA vaccine encoding alpha-fetoprotein/heat shock protein 70

Abstract: AIM:To construct a DNA vaccine encoding human alphafetoprotein (hAFP)/heat shock protein 70 (HSP70), and to study its ability to induce specific CTL response and its protective effect against AFP-expressing tumor. METHODS:A DNA vaccine was constructed by combining hAFP gene with HSP70 gene. SP2/0 cells were stably transfected with pBBS212-hAFP and pBBS212-hAFP/HSP70 eukaryotic expression vectors. Mice were primed and boosted with DNA vaccine hAFP/HSP70 by intramuscular injection, whereas plasmid with hAFP or H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…Universally applicable novel HSP-mediated strategies have been devised because of limitations with isolation of HSPs from tumor as autologous vaccine (Castelli et al 2004;Gordon and Clark 2004). One of the strategies taken so far is DNA vaccination using HSP70 gene fused to or co-administered with a candidate antigen (Chen et al 2000;Geng et al 2006;Hsu et al 2001;Kim et al 2005;Lan et al 2007;Li et al 2006Li et al , 2007Liso et al 2005;Ma et al 2005;Pavlenko et al 2004;Wang et al 2004;Ye et al 2004;Zhang and Huang 2006;Zhang et al 2007). One study demonstrated that DNA vaccine containing HSP70 fused to C-terminal domain of Her2/neu could combat an aggressive Her2-expressing tumor (Kim et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Universally applicable novel HSP-mediated strategies have been devised because of limitations with isolation of HSPs from tumor as autologous vaccine (Castelli et al 2004;Gordon and Clark 2004). One of the strategies taken so far is DNA vaccination using HSP70 gene fused to or co-administered with a candidate antigen (Chen et al 2000;Geng et al 2006;Hsu et al 2001;Kim et al 2005;Lan et al 2007;Li et al 2006Li et al , 2007Liso et al 2005;Ma et al 2005;Pavlenko et al 2004;Wang et al 2004;Ye et al 2004;Zhang and Huang 2006;Zhang et al 2007). One study demonstrated that DNA vaccine containing HSP70 fused to C-terminal domain of Her2/neu could combat an aggressive Her2-expressing tumor (Kim et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…How to enhance host's active immunity to AFP may be an interesting strategy for HCC therapy. Previous studies on AFP specific immunothereapy for HCC included AFP plasmid immunization, AFP-transduced dendritic cells (DCs) immunization and AFP plasmid prime-AFP adenovirus boost immunization [10][11][12][13][14]. AFP plasmid immunization produced detectable but low levels of AFP specific T cell responses and poorly reproducible protective immunity [4][5][6][7].…”
Section: Resultsmentioning
confidence: 99%
“…However, the need for costly cell culture procedures limited their wide availability for clinical use, and the unstable culture technique might yield tolerating vaccine [15]. AFP plasmid prime-AFP adenovirus boost immunization could engender significant AFP specific T-cell responses and protective immunity in mice [12,13]. But the miscellaneous procedures precluded their use.…”
Section: Resultsmentioning
confidence: 99%
“…3 Activation of an HCC-specific immune response can be accomplished by targeting tumor-associated self-antigens. In contrast to the immunotherapy using coimmunization with an AFP DNA vaccine and an immune response stimulator, such as, heat-shock protein70 20 and CTLA4, 21 the attenuated S. typhimurium oral DNA vaccines provide dual effects in one administration. The attenuated S. typhimurium not only serves as a DNA vaccine delivery vehicle but also an immune response stimulator.…”
Section: Discussionmentioning
confidence: 99%